The Influence of Kap Quality and Audit Opinion on Audit Delay with The Audit Commission as a Moderating Variable - Ayu Purnamasari, Ajeng; Rahma Sari, Intan (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
This research aims to determine the effect of KAP quality and audit opinion on audit delay, using audit fees as a moderating variable. The population covered by this research consists of infrastructure companies listed on the Indonesian Stock Exchange (2018-2022). Based on purposive sampling method. , the total sample obtained was 33 respondents with a total of 165 data points over 5 years. This research is a type of quantitative research with the secondary data collection method used is secondary data, which is existing data produced by previous researchers using quantitative methods. The hypothesis testing in this research uses the multiple linear regression analysis method developed through 10 reviews. Based on the test results, it was found that KAP quality (X1) has no effect on audit delay, audit opinion (X2) has a negative effect on audit delay, audit fees audits do not moderate the effect of KAP quality on audit delay and audit fees are able to moderate the influence of audit opinion on audit delay